(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study was conducted in 2025 in the city of Sabha, Libya, targeting five bakeries selected randomly from the city center, as this geographical area represents the highest population density. The primary objective was to assess the quality of water utilized in bread production by analyzing samples collected from the water sources used in these bakeries. A total of five samples were collected, with three replicates per sample. These samples underwent a series of chemical and microbiological analyses. Upon arrival at the laboratory, microbiological quality tests were performed; the total plate count (TPC) results indicated bacterial growth ranging from 0 to 100 CFU/ml. These values fall within the permissible limits set by the Libyan Standards and the World Health Organization (WHO) guidelines. Additionally, all samples were found to be free of coliform bacteria. Regarding the chemical analysis, parameters measured included alkalinity, total hardness (TH), chloride ions, nitrates, and pH levels, in addition to Total Dissolved Solids (TDS), calcium, magnesium, copper, zinc, sodium, and potassium. The results showed that pH values ranged between 6.5 and 7, with an average of 6.75, which is within the allowable limits of the Libyan Standards and WHO. However, the measured TDS values ranged from 27 to 3307 mg/L, with an average of 1667 mg/L. These concentrations are considered high compared to the Libyan and WHO standards; only sample No. 1 was found to be compliant. Such high salinity levels negatively impact the texture and flavor of the produced bread. Furthermore, measured alkalinity values ranged from 8 to 149 mg/L (average 98 mg/L), while chloride levels ranged from 15.5 to 887.7 mg/L. The concentrations for nitrates, total hardness, calcium, magnesium, copper, sodium, and potassium ranged between (10–182), (3–100), (20–769.3), (2–220), (4–53), (0–0.00565), (4–170), and (2–91) mg/L, respectively. Finally, all samples tested negative for the presence of zinc.